Distribution of major diseases of shallot in South Kalimantan, Indonesia - SAFITRI, YUNIEKA AULIA; HASANAH, USWATUN; SALAMIAH, SALAMIAH; SAMHARINTO, SAMHARINTO; PRAMUDI, M INDAR (Asian Journal of Agriculture, 2019)
Abstract. Safitri YA, Hasanah U, Salamiah, Samharinto, Pramudi MI. 2019. Distribution of major diseases of shallot in South Kalimantan, Indonesia. Asian J Agric 3: 33-40. Shallot is a vegetable crop with high economic value, but its productivity in Indonesia is still relatively low. One of the causes is due to attack of the diseases. The research was conducted from November 2017 to April 2018, with the purpose of studying the distribution of major diseases of shallots in South Kalimantan. It consisted of field, laboratory, and greenhouse research. Field research involved the survey of shallots’ extensive planting in eight villages of six districts in South Kalimantan, disease symptoms, the broad of attack, and the collection of secondary data. Laboratory research included the isolation and identification of the pathogen causing diseases. The greenhouse research was conducted to perform the Postulate Koch test. The research result showed that there were two major diseases of shallots, namely Moler and Anthracnose. Pathogen causing Moler disease (Fusarium oxysporum) attacked shallot plant in six districts (Tabalong, Balangan, Tanah Laut, Kotabaru, Tapin, and Banjarbaru) and pathogen causing Anthracnose disease (Colletotrichum sp) attacked shallot plant in five districts (Tabalong, Balangan, Tanah Laut, Kotabaru, and Tapin).